2015
DOI: 10.5937/inovacije1502089m
|View full text |Cite
|
Sign up to set email alerts
|

Necessity of religious education for development of the whole personality

Abstract: UDC 27-75:159.923 Иновације у настави, XXVIII, 2015/2, стр. 89-96 37.017.93 др Бошко Миловановић данашње време запажамо активности новог историјско-методичко-педагошког пок-рета, заснованог на идејама персонализоване, индивидуализоване и диференциране наста-ве, као и субјективистичког приступа који уче-ника ставља у средиште образовног процеса. Те идеје и стремљења су вредни, уколико их посма-трамо у односу на наше запарложено школство, и поред свих опасности које прате деловање по-менутог покрета. Опасн… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Promoting the application of the salutogenetic model of health is of crucial importance, as it is readily apparent that this model of health has become increasingly important and widely applicable in numerous fields and to diverse age groups over the last few decades [21]. Numerous surveys conducted by salutogenetic-oriented researchers, who found that there was a positive correlation of the sense of coherence and family sense of coherence with a series of diverse indicators of mental health and functioning of the individual and family, bear witness to the above mentioned [21][22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Promoting the application of the salutogenetic model of health is of crucial importance, as it is readily apparent that this model of health has become increasingly important and widely applicable in numerous fields and to diverse age groups over the last few decades [21]. Numerous surveys conducted by salutogenetic-oriented researchers, who found that there was a positive correlation of the sense of coherence and family sense of coherence with a series of diverse indicators of mental health and functioning of the individual and family, bear witness to the above mentioned [21][22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%